(untitled) (Shahroud Journal of Medical Sciences, 2021)
Background: Nowadays, cancer is one of the most critical health problems. The present study aimed to investigate the impact of the Johnson Behavioral Model on the anxiety of mothers of children with cancer. Methods: This empirical study was done on 66 mothers of children with cancer in the centers covered by children with cancer in 2020. The samples were selected using simple random sampling. Data were collected using the Spielberger demographic and anxiety inventory. After data collection, data analysis was done in SPSS18 using descriptive statistics and independent t-test, paired t-test, chi-square test, fisher, and covariance test. The significant level was set at 0.05. Results: The anxiety level was equal to 112.39±18.22 and 111±20.07 before intervention and equal to 81.21±6012 and 108.42±18.37 after the intervention in the intervention and control group, respectively. The independent t-test showed no significant difference between the two groups before the intervention (Pvalue=0.769). However, the difference was significant after the intervention (Pvalue<0.01). The paired t-test showed a significant difference between the two groups before and after the intervention in the intervention (Pvalue=0.001) and control (Pvalue<0.001) groups. Conclusions: The results obtained from this study showed that the Johnson theory plays a key role in reducing the anxiety of mothers of children with cancer. Keywords: Johnson Behavioral Model, Anxiety, Mothers of children, Cancer